A multicenter observational survey of management strategies in 442 pregnancies with suspected placenta accreta spectrum. (2nd April 2021) - van Beekhuizen, Heleen J.; Stefanovic, Vedran; Schwickert, Alexander; Henrich, Wolfgang; Fox, Karin A.; MHallem Gziri, Mina; Sentilhes, Loïc; Gronbeck, Lene; Chantraine, Frederic; Morel, Oliver; Bertholdt, Charline; Braun, Thorsten; et al.
Abstract: Introduction: Management options for women with placenta accreta spectrum (PAS) comprise termination of pregnancy before the viable gestational age, leaving the placenta in situ for subsequent reabsorption of the placenta or delayed hysterectomy, manual removal of placenta after vaginal delivery or during cesarean section, focal resection of the affected uterine wall, and peripartum hysterectomy. The aim of this observational study was to describe actual clinical management and outcomes in PAS in a large international cohort. Material and methods: Data from women in 15 referral centers of the International Society of PAS (IS‐PAS) were analyzed and correlated with the clinical classification of the IS‐PAS: From Grade 1 (no PAS) to Grade 6 (invasion into pelvic organs other than the bladder). PAS was usually diagnosed antenatally and the operators performing ultrasound rated the likelihood of PAS on a Likert scale of 1 to 10. Results: In total, 442 women were registered in the database. No maternal deaths occurred. Mean blood loss was 2600 mL (range 150‐20 000 mL). Placenta previa was present in 375 (84.8%) women and there was a history of a previous cesarean in 329 (74.4%) women. The PAS likelihood score was strongly correlated with the PAS grade ( P < .001). The mode of delivery in the majority of women (n = 252, 57.0%) was cesarean hysterectomy, with a repeat laparotomy in 20 (7.9%) due to complications. In 48 women (10.8%), the placenta was intentionally left in situ, of those, 20 (41.7%) had a delayed hysterectomy. In 26 women (5.9%), focal resection was performed. Termination of pregnancy was performed in 9 (2.0%), of whom 5 had fetal abnormalities. The placenta could be removed in 90 women (20.4%) at cesarean, and in 17 (3.9%) after vaginal delivery indicating mild or no PAS. In 34 women (7.7%) with an antenatal diagnosis of PAS, the placenta spontaneously separated (false positives). We found lower blood loss ( P < .002) in 2018‐2019 compared with 2009‐2017, suggesting a positive learning curve. Conclusions: In referral centers, the most common management for severe PAS was cesarean hysterectomy, followed by leaving the placenta in situ and focal resection. Prenatal diagnosis correlated with clinical PAS grade. No maternal deaths occurred.